Can Inflation Forecast and Monetary Policy Path be Really Useful? The Case of Czech Republic - Magdalena Szyszko; Karolina Tura (Institute of Economic Research (IER), 2014)
Producing and revealing inflation forecasts is believed to be the best way of implementing a forward-looking monetary policy. The article focuses on inflation forecast targeting (IFT) at the Czech National Bank (CNB) in terms of its efficiency in shaping consumers' inflation expectations. The goal of the study is to verify accuracy of the inflation forecasts, and their influence on inflation expectations. The research is divided into four stages. At the first stage central bank credibility is examined. At the second stage - accuracy of the inflation forecasts. The next step covers a qualitative analysis of IFT implementation. Finally the existence of the interdependences of inflation forecast, optimal policy paths and inflation expectations are analyzed. Credibility of the central bank, accuracy of the forecast and decision-making procedures are the premises for the existence of relationship between forecasts and expectations. The research covers July 2002 - end of 2013. Its methodology includes the qualitative analysis of decision-making of the CNB, quantitative methods (Kia and Patron formula, MAE forecasts errors, quantification of expectations, non-parametric statistics). The results show the existence of interdependences between inflation forecasts and expectations of moderate strength. The preconditions of such interdependences are partially fulfilled. The research opens the field for cross-country comparisons and for quantification of IFT implementation.
Keywords: E52; E58; E61; 330; inflation forecasts; inflation forecast targeting; policy path; inflation expectations